CAN RELIGIOUS SUPERIORS IMPOSE NON-PENAL CORRECTIVE MEASURES ON THEIR SUBJECTS WITHOUT RESORTING TO PENAL SANCTIONS? - Kokkaravalayil, Sunny Thomas (50. anniversario della fondazione della Facoltà di diritto canonico Orientale del PIO, 1971-2021, 2023)
The article revolves round the question whether religious superiors of Eastern Catholic Churches are legally competent to impose administrative sanctions on their subjects when needed. A review of the characteristics of the Eastern Catholic penal law (which is the content of this article's first part) gives us a good introduction to the topic. Having analysed various CCEO canons (in the second part), we can say that competent religious superiors, even though they do not have the ordinary power of governance, have the legal capacity to impose administrative sanctions on their subjects in order to correct their improper behaviour, without having recourse to canonical penalty, the imposition of which is highly restricted by law. This capacity of superiors, albeit not explicit in CCEO because of the absence of a norm like CIC c. 1312 §3, is to be deduced from various canons and long-standing practice.